Chromosome painting facilitates anchoring reference genome sequence to chromosomes In Situ and integrated karyotyping in banana (Musa Spp.) - Šimoníková, D.; Němečková, A.; Karafiátová, M.; Uwimana, Brigitte; Swennen, Rony L.; Doležel, Jaroslav; Hřibová, E. (Frontiers Media, 2019)
Oligo painting FISH was established to identify all chromosomes in banana (Musa spp.) and to anchor pseudomolecules of reference genome sequence of Musa acuminata spp. malaccensis “DH Pahang” to individual chromosomes in situ. A total of 19 chromosome/chromosome-arm specific oligo painting probes were developed and were shown to be suitable for molecular cytogenetic studies in genus Musa. For the first time, molecular karyotypes of diploid M. acuminata spp. malaccensis (A genome), M. balbisiana (B genome), and M. schizocarpa (S genome) from the Eumusa section of Musa, which contributed to the evolution of edible banana cultivars, were established. This was achieved after a combined use of oligo painting probes and a set of previously developed banana cytogenetic markers. The density of oligo painting probes was sufficient to study chromosomal rearrangements on mitotic as well as on meiotic pachytene chromosomes. This advance will enable comparative FISH mapping and identification of chromosomal translocations which accompanied genome evolution and speciation in the family Musaceae.